COMPETENCY DEVELOPMENT AND BUSINESS GRADUATE EMPLOYABILITY SKILLS: MODERATION BY ACADEMIC ACHIEVEMENT ON THEORY OF COGNITIVE APPRENTICESHIP - Bishanani Omar; Hutkemri Zulnaidi; Norlidah Alias (MOJES: Malaysian Online Journal of Educational Sciences, 2024)
This research aims to examine the moderation effect of academic achievement in the relationship between competency development and business graduate employability skills at vocational colleges in Malaysia. Applying a purposive sampling method, data were gathered among students studying business programs at vocational colleges in Malaysia and were analyzed using Smart Partial Least Squares (PLS). The findings indicated significant positive associations between competency development and business graduate employability skills at vocational colleges in Malaysia. Meanwhile, academic achievement was the opposite as there was an insignificant effect towards the business graduate employability skills for vocational colleges. Academic achievement has not moderated the relationship between competency development and business graduate employability skills for vocational colleges. It is expected that this study could provide a better understanding of the need of industry for competency development for business graduate employability skills for vocational colleges and institutions improving students’ academic achievement.